Peran Media Sosial dalam Pencegahan dan Penindakan Tindak Pidana Korupsi di Indonesia - Zainudin Hasan; Rayhan Triantara Mahdi; Anugrah Ziando Alfarizi; Muhammad Aric Savero (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
The corruption case in the BTS 4G project by the Ministry of Communication and Information Technology (Kominfo), which involved the misuse of funds in the construction of BTS towers in Indonesia's 3T (underdeveloped, frontier, and outermost) regions, has become a major public concern in recent years. The Rp 9.8 trillion project is suspected to have been misappropriated by several officials involved. This study aims to examine the role of social media in increasing public participation in the monitoring and mitigation of the corruption case. The research method used is a descriptive qualitative approach combined with social media analysis. The findings show that social media plays a significant role in accelerating the dissemination of information related to the BTS 4G corruption case, raising public awareness, and exerting social pressure on law enforcement agencies to take action. Furthermore, social media also facilitates digital activism, which mobilizes public support and strengthens oversight of government policies. This study concludes that social media serves as an effective tool for social control, although it also faces challenges in terms of the spread of hoaxes and disinformation.